Comparative effects of narrow vs. wide cuff blood flow restriction on muscle synergy dynamics: a time-frequency decomposition approach - Chang, S.; Hu, C. (Sensors, 2025)
Blood Flow Restriction Training (BFRT) is a training method typically performed with low-intensity loads, yet it has been shown to induce muscle growth and strength gains similar to those achieved through high-load resistance training. This study investigates how different cuff widths affect muscle activation and synergy during squat exercises under BFRT conditions, using wavelet packet transform combined with non-negative matrix factorization (WPT-NNMF) for time-frequency analysis of muscle synergy. Fifteen male participants, each with more than three years of resistance training experience, performed squats under three conditions: non-BFRT (Non-BFRT), BFRT with a 5 cm cuff (5 cm-BFRT), and BFRT with a 10 cm cuff (10 cm-BFRT), all at 30% of their one-repetition maximum (1RM). Surface electromyography (sEMG) signals were recorded from eight lower-limb muscles, and muscle synergy patterns were analyzed using NNMF and WPT-NNMF. The results showed that, compared to Non-BFRT, the 10 cm-BFRT condition significantly increased activation in the vastus lateralis (VL), gluteus maximus (GM), tibialis anterior (TA), and lateral gastrocnemius (GL), while the 5 cm-BFRT decreased activation in the biceps femoris (BF) and increased TA activation. Muscle synergy analysis revealed three distinct synergy modules across all conditions, with the total number of synergies remaining stable. However, the activation weights of muscles within these modules varied across different squat phases, suggesting adaptive neuromuscular regulation under different BFRT conditions. The time-frequency synergy analysis highlighted dynamic changes in muscle coordination across time scales and frequency bands under various training conditions. The number of muscle synergies showed significant changes across different time-frequency regions, with a marked decrease in the 120-250 Hz frequency range in the 5 cm-BFRT condition compared to Non-BFRT. This study is the first to apply time-frequency muscle synergy analysis to investigate the effects of cuff width on neuromuscular coordination during BFRT. The findings offer new insights into the time-frequency characteristics of muscle synergy under BFRT conditions and enhance the understanding of neuromuscular control and motor execution in blood flow restriction training.